Delimitação do usuário nas etapas de criação, modelagem e prototipagem do produto de vestuário (ModaPalavra e-periódico, 2017)
Because of complaints of clothes that do not fit well and bother, oreven the difficulty of acquiring a suitable outfit for an occasion, to the clothing industry may be failing to consider the user in developing their products. The aim of this paper was to determine whether the steps for creating, modeling and prototyping of garment products the user is being considered, as for a design project is right to consider it at all stages of development. For this a literature review and interviews with professionals was held. With the results we can see the difficulty that professionals have to define the public to create the pieces. We also found that most professionals understand the importance of measures table however end up adjusting the empirically, and the realization of prototype testing many choose models that does not match the reality of the public company.
Keywords: fashion design; development of clothing; user